Simultaneous removal of turbidity, suspended solids and chemical oxygen demand from carwash effluent using aluminium electrodes in monopolar mode electrocoagulation - Muyarip, A; Aziz, N A A (2023)
The growth of car wash centres across the country increases every year due to the increase in the number of vehicles needed to meet transportation demands for daily affairs. Therefore, there is a concern about releasing carwash wastewater (CWW) into the drainage system and waterways without proper treatment. This is a problem for small and medium enterprises that lack the financial budget to provide a suitable treatment system for a car wash centre. The effects of hazardous contaminant emissions can harm ecology and public health. Electrocoagulation using aluminium (Al) electrodes is expected to replace the use of chemicals in the coagulation system that will leave harmful secondary residues and be expensive in terms of cost. With that, this experimental work was conducted to investigate the effectiveness of electrocoagulation using Al electrodes to eliminate target contaminants such as turbidity, suspended solids (SS), and chemical oxygen demand (COD) from CWW. This study involves using Al electrodes arranged in a monopolar manner and connected to a power supply with a maximum current of 2.0 A. CWW samples were collected from car wash centres around Parit Raja, Batu Pahat. Several operating parameters, such as current density, initial pH, and electrocoagulation time, have been selected to determine the optimum conditions for EC treatment methods specifically designed to treat CWW. The results of the study exhibit that the optimum conditions have been determined at a current density of 29 A/m2, CWW initial operating pH of 8 and an electrocoagulation time of 70 minutes to achieve the highest level of uptake for turbidity (91.2% removal), SS (82.7% removal) and COD (64.8% removal). These findings underline the ability of this treatment method to remove targeted contaminants from CWW. This study contributes to developing a treatment technique that is more practical for treating CWW. In addition, this study also has important implications in mitigating water pollution, preventing ecosystem damage, and reducing health-related risks due to improper discharge of CWW